The liquid glass as one of the factors which influence on hardness of plaster patterns - Hajduga, Maciej; Wątor, Agnieszka; Suchoń, Marian (European Journal of Clinical and Experimental Medicine, 2005)
<span style="color: #010101; font-family: Lato, sans-serif; font-size: 14px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-align: justify; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">In the elaboration have been described different methods of the hardening. The investigations have been carried out on samples, which after drying, were treated by surface hardening, using: soda liquid glass, Die Hardener and Shera Brillant. They have also been made samples of gypsum plaster of the 3rd and 4th hardness class, in order to compare their hardness with the hardness of samples with surface hardening. All samples have been made subject to control of hardness, using the Shore A-type hardness tester. The obtained results say that the best results are obtained by using hardening substances, such as Die Hardener or Shera Brillant.